Molecular cloning of the MARCH family in grass carp (Ctenopharyngodon idellus) and their response to grass carp reovirus challenge. Issue 63 (April 2017) - Ou, Mi; Huang, Rong; Xiong, Lv; Luo, Lifei; Chen, Geng; Liao, Lanjie; Li, Yongming; He, Libo; Zhu, Zuoyan; Wang, Yaping
Abstract: Grass carp ( Ctenopharyngodon idellus ) is an economical aquaculture species in China, and the Grass Carp Reovirus (GCRV) that causes hemorrhagic disease seriously affects the grass carp cultivation industry. Substantial evidence indicates that there is an association between the membrane-associated RING-CH family of E3 ligase (MARCH) family and immune defense in mammals, while functional studies on non-mammalian MARCH proteins are limited. In order to know the characteristics of the MARCH genes in C. idellus, eight MARCH genes ( MARCH1, 2, 5, 6, 7, 8, 9 and 11 ) were cloned and the open reading frames (ORF) were identified in grass carp. All MARCH proteins in grass carp contained an RING-CH domain, which is characteristic of the MARCH protein. The phylogenetic analysis revealed that different MARCH proteins gathered into their separate clusters. All eight members of the MARCH gene family were detected in all tissues sampled, but the relative expression level differed. In addition, the mRNA expression of all the MARCHs was regulated at different levels in the immune organs after a GCRV challenge, and they responded robustly in both the intestine and liver. The mRNA expression of MARCH8, MHC II, TfR, IL1RAP, EGR1, and DUSP1 in the intestine after GCRV infection was analyzed, and the results showed that MARCH8 could negatively regulate TfR, IL1RAP, EGR1, and DUSP1, which signaled via the MAPK or NF-κB-activation pathways that play vital roles in immunity. Our findings identified a novel gene family in C. idellus and provided novel evidence that MARCH genes are inducible and involved in the immune response. Moreover, MARCH8 might function to negatively regulate immune receptors in C. idellus . Therefore, the MARCH might play a vital role in regulating the immune response of C. idellus . Highlights: Eight MARCH genes in C. idellus were cloned, and all the MARCH proteins contained an RING-CH domain. MARCH genes responded substantially after GCRV challenge, especially for MARCH1 and MARCH8 . MARCH8 might function to negatively regulate immune receptors in C. idellus. The MARCH family might play a vital role in regulating the immune response of C. idellus.